Annotated record of the detailed examination of ferromanganese crusts from the Galapagos Ridge area - Gary R Byerly; William G Melson; Peter R Vogt (PANGAEA, 1976)
Volcanic rocks, dredged from depths greater than 1000 m on the Galapagos spreading center, show extreme chemical diversity, including rhyodacites, andesite, ferro-basalts, and low-K oceanic tholeiite. All samples have fresh glassy margins. The ferro-basalts contain up to 18.5% total iron as FeO and up to 3.75% TiO2, while the oceanic tholeiites are as low as 0.02% K2O. The ferro-basalts correlate with the previously proposed zone of high magnetic anomaly amplitudes which flank the Galapagos hot spot, and are consistent with a genesis by shallow fractional crystallization.
Supplement to: Byerly, GR et al. (1976): Rhyodacites, andesites, ferro-basalts and ocean tholeiites from the galapagos spreading center. Earth and Planetary Science Letters, 30(2), 215-221, https://doi.org/10.1016/0012-821X(76)90248-X